The Impact of Job Security on Contextual Performance: An Applied Study of Workers in the Bish Municipality in the Kingdom of Saudi Arabia - Hawaz, Abdolaziz Essa; Alariki, Baseim Qaid (Journal of Economic, Administrative and Legal Sciences, 2025)
The aim of this research is to identify the impact of job security on contextual performance in its two dimensions (organizational commitment and organizational citizenship behavior) among employees in the Baish Municipality in the Kingdom of Saudi Arabia, and to identify the statistical differences in the respondents' responses regarding the impact of job security on contextual performance of employees in the Baish Municipality according to the following personal and functional variables: (gender, age, educational qualification, length of service), as well as to determine the level of feeling of job security among employees in the Baish Municipality in the Kingdom of Saudi Arabia, and to determine the level of contextual performance among employees in the Baish Municipality in the Kingdom of Saudi Arabia. The study population represented all employees in the Baish Municipality, numbering 150. The researcher used the comprehensive enumeration method as it is the most appropriate method for the size of the population and the nature of the research. The researcher received 132 responses via the electronic link. The study relied on the descriptive analytical approach. The results of the statistical analysis revealed a statistically significant positive effect at the level of α≤0.05 of job security on contextual performance in its two dimensions (organizational commitment and organizational citizenship behavior) among employees in the Baish Municipality in the Kingdom of Saudi Arabia. The study also found no statistically significant differences among the respondents regarding the impact of job security on contextual performance of employees in the Baish Municipality in the Kingdom of Saudi Arabia according to the following personal and occupational variables: (gender, age, educational qualification, length of service). The results also indicated that the job security axis, the organizational commitment axis, and the organizational citizenship behavior axis were moderate, with the arithmetic mean percentage for each of them being 66.54%, 66.24%, and 64.44%, respectively.
Keywords: Job security; contextual performance; organizational commitment; organizational citizenship behavior